2020
DOI: 10.1186/s12936-020-03456-6
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variations in histidine-rich protein 2 and histidine-rich protein 3 of Myanmar Plasmodium falciparum isolates

Abstract: Background Malaria rapid diagnostic tests (RDTs) are precious tools to diagnose malaria. Most RDTs used currently are based on the detection of Plasmodium falciparum histidine-rich protein 2 (PfHRP2) in a patient’s blood. However, concern has been raised in recent years that deletion of pfhrp2 in the parasite could affect the accuracy of PfHRP2-based RDTs. In addition, genetic variation in pfhrp2 might influence the accuracy and sensitivity of RDTs. In this study, the genetic variation in pfhrp2 and pfhrp3 in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…Pfhrp3 sequences showed less diversity in terms of amino-acid sequences than pfhrp2 , as reported previously [ 60 ]. Similar to previous studies, the most frequent and repeated type was type 16 [ 64 , 65 ], and type 17 showed a marked variation, as in Kenya [ 61 ], thus suggesting a high antigenicity and that it may be useful for RDT detection.…”
Section: Discussionsupporting
confidence: 85%
“…Pfhrp3 sequences showed less diversity in terms of amino-acid sequences than pfhrp2 , as reported previously [ 60 ]. Similar to previous studies, the most frequent and repeated type was type 16 [ 64 , 65 ], and type 17 showed a marked variation, as in Kenya [ 61 ], thus suggesting a high antigenicity and that it may be useful for RDT detection.…”
Section: Discussionsupporting
confidence: 85%
“…Theoretically, this means that infections caused by parasites that carry histidine rich proteins deletion mutation (HRP2) could have been missed. However, the rate of PfHRP2 deletion has been reported to be very low in Myanmar (40,41).…”
Section: Discussionmentioning
confidence: 98%
“…Theoretically, this means that infections caused by parasites that carry histidine rich proteins deletion mutation (HRP2) could have been missed. However, the rate of Pf HRP2 deletion has been reported to be very low in Myanmar [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%